1998
DOI: 10.1074/jbc.273.15.9234
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Complex Formation of SHPS-1 with SHP-2 in Insulin-stimulated Mitogen-activated Protein Kinase Activation

Abstract: SHPS-1 is a receptor-like protein that undergoes tyro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
111
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 54 publications
(58 reference statements)
4
111
0
Order By: Relevance
“…SHP-2 is proposed as a positive mediator of cell growth and its recruitment to the plasma membrane upon growth stimulation has been observed (Stein-Gerlach et al, 1998). Takada et al (1998) reported that overexpression of SHPS-1 enhanced insulin-induced activation of MAP kinase, and mutation in tyrosine residues, Tyr449 and Tyr473, abolished the tyrosine phosphorylation of SHPS-1, its association with SHP-2 and activation of MAP kinase. In this study, however, we showed evidence that tyrosine phosphorylation of SHPS-1 was elevated in c-Src3Y1, G2E3Y1 and G2A3Y1, all of which are not transformed, while net amount of tyrosine phosphorylated SHPS-1 was substantially decreased in SR3Y1 (Figure 6a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SHP-2 is proposed as a positive mediator of cell growth and its recruitment to the plasma membrane upon growth stimulation has been observed (Stein-Gerlach et al, 1998). Takada et al (1998) reported that overexpression of SHPS-1 enhanced insulin-induced activation of MAP kinase, and mutation in tyrosine residues, Tyr449 and Tyr473, abolished the tyrosine phosphorylation of SHPS-1, its association with SHP-2 and activation of MAP kinase. In this study, however, we showed evidence that tyrosine phosphorylation of SHPS-1 was elevated in c-Src3Y1, G2E3Y1 and G2A3Y1, all of which are not transformed, while net amount of tyrosine phosphorylated SHPS-1 was substantially decreased in SR3Y1 (Figure 6a).…”
Section: Discussionmentioning
confidence: 99%
“…SHPS-1 is a receptor-like protein associated with protein tyrosine phosphatases with two SH2 domains, SHP-1 and SHP-2. SHPS-1 has three immunoglobulin-like domains in its extracellular region and four YXX(L/V/I) motifs, tyrosine phosphorylation sites of which Tyr449 and Tyr473 are critical for SHP-2 binding, in its cytoplasmic region (Takada et al, 1998). Various mitogens such as epidermal growth factor (EGF), insulin and platelet derived growth factor (PDGF) induced tyrosine phosphorylation of SHPS-1 and its association with SHP-2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of mechanisms of PTP binding to ITIM motifs may shed light on PTP functional regulation, since little is known regarding the recruitment and activation of PTPs under physiologic conditions. SIRP/SHPS-1 proteins are tyrosine phosphorylated in response to EGF and insulin, and were originally identi®ed in anti-SHP2 immunoprecipitates (Fujioka et al, 1996;Kharitonenkov et al, 1997;Takada et al, 1998). Integrin signaling also increases SHPS-1 tyrosine phosphorylation and SHP2 binding , suggesting that SIRP/SHPS-1 proteins modulate cell signaling in response to both soluble growth factors and cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these ®ndings suggest that multiple RTK-induced pathways may be downstream targets of SIRP. SIRP has been experimentally shown to modulate signaling of many RTKs, including the insulin receptor and the Epidermal Growth Factor Receptor (EGFR) (Kharitonenkov et al, 1997;Takada et al, 1998). SIRP tyrosine phosphorylation and subsequent recruitment of SHP2 to the plasma membrane have been shown to be related to SIRP functional regulation of RTK signaling (Cambier, 1997;Kharitonenkov et al, 1997).…”
Section: Introductionmentioning
confidence: 99%